Epidemiology of myelodysplastic syndromes: Why characterizing the beast is a prerequisite to taming it. (March 2019) - Zeidan, Amer M.; Shallis, Rory M.; Wang, Rong; Davidoff, Amy; Ma, Xiaomei
Abstract: Myelodysplastic syndromes (MDS) consist of a heterogeneous group of myeloid neoplasms characterized by inefficient hematopoiesis, variable cytopenias and a considerable risk of progression to acute myeloid leukemia. Epidemiological assessment of MDS has been hampered by evolving diagnostic criteria and delayed classification of MDS as cancers until 2001. The poorly-understood nature of these neoplasms combined with the lack of effective therapies for decades contributed to suboptimal case ascertainment and underreporting. The annual age-adjusted incidence in the United States is approximately 4.0/100, 000 persons, and the incidence substantially rises with age. Beyond age, other risk factors include male gender, obesity, smoking, and prior receipt of radiotherapy or chemotherapy, but most cases remain idiopathic in nature. The overall 5-year survival probability remains relatively poor at approximately 31% without a clear temporal improvement in outcomes despite the approval of three MDS-specific therapies since 2004 and increasing use of allogeneic hematopoietic stem cell transplantation. Better understanding of epidemiological trends of MDS will likely require incorporation of the key genetic determinants of the disease into consistent diagnostic paradigms that go beyond traditional morphologic assessments. The heterogeneity of the disease and lack of uniformly-defined genetic markers makes such a task difficult. Thorough case ascertainment and reporting efforts can provide vital insights that could inform treatment decisions and eventually improve the outcomes of patients with MDS.